Assessing ground stability of a vertical backfilled stope considering creep behaviors of surrounding rocks - Ruofan Wang; Lang Liu; Mengbo Zhu; Huafu Qiu; Bingbing Tu; Huisheng Qu; Hao Cui (Journal of Rock Mechanics and Geotechnical Engineering)
Backfill is often employed in mining operations for ground support, with its positive impact on ground stability acknowledged in many underground mines. However, existing studies have predominantly focused only on the stress development within the backfill material, leaving the influence of stope backfilling on stress distribution in surrounding rock mass and ground stability largely unexplored. Therefore, this paper presents numerical models in FLAC3D to investigate, for the first time, the time-dependent stress redistribution around a vertical backfilled stope and its implications on ground stability, considering the creep of surrounding rock mass. Using the Soft Soil constitutive model, the compressibility of backfill under large pressure was captured. It is found that the creep deformation of rock mass exercises compression on backfill and results in a less void ratio and increased modulus for fill material. The compacted backfill conversely influenced the stress distribution and ground stability of rock mass which was a combined effect of wall creep and compressibility of backfill. With the increase of time or/and creep deformation, the minimum principal stress in the rocks surrounding the backfilled stope increased towards the pre-mining stress state, while the deviatoric stress reduces leading to an increased factor of safety and improved ground stability. This improvement effect of backfill on ground stability increased with the increase of mine depth and stope height, while it is also more pronounced for the narrow stope, the backfill with a smaller compression index, and the soft rocks with a smaller viscosity coefficient. Furthermore, the results emphasize the importance of minimizing empty time and backfilling extracted stope as soon as possible for ground control. Reduction of filling gap height enhances the local stability around the roof of stope.